Cahiers du Sud : poésie-critique-philosophie. (Marseille, 1932)
Bibliotheek E. Anseele
Hoofdredactie: Cours du Vieux Port 10, Marseille / Thérèse Aubray, Gaston Baissette, Gabriel Bertin, Joe Bousquet, Marcel Brion, Henri Flachère, Léon-Gabriel Gros, Gaston Maurin (Conseil de Rédaction)Beheer/Administratie: Cours du Vieux Port 10, Marseille / Agence générale : Librairie José Corti, rue de Clichy 6, Paris
Drukker/Drukkerij: Imp. Mistral, Cavaillon
Frans
Periodiek
Keywords: cultuur; Frankrijk